Role of IL-17 in plaque psoriasis: therapeutic potential of ixekizumab - Hanley TL; Yiu ZZN (Therapeutics and Clinical Risk Management, 2017)
Tessa L Hanley,1 Zenas ZN Yiu2,3 1Fairfield General Hospital, Bury, 2Centre for Dermatology, 3Centre for Pharmacoepidemiology and Drug Safety, Manchester Academic Health Science Centre, Manchester, UK Abstract: Developments in the understanding of the immunopathogenesis of psoriasis have identified interleukin (IL)-17 as the key proinflammatory cytokine in the pathogenesis of plaque psoriasis, with the consequent development of drugs that target this cytokine or associated receptors. Ixekizumab is a subcutaneously administered humanized monoclonal antibody, which acts to neutralize IL-17A. This article reviews the role of IL-17 in the pathogenesis of psoriasis, the biological and pharmacokinetics of ixekizumab and the safety profile and the clinical efficacy of ixekizumab in Phase III clinical trials. Phase III clinical trials of ixekizumab have so far demonstrated excellent early clinical efficacy, with a comparable safety profile to the existing biologic therapies for psoriasis. To further assess its position in the treatment algorithm for psoriasis, a further head to head RCT with secukinumab could be established, alongside comparative effectiveness studies from observational research. In addition, trials are needed to assess its role in those with tumor necrosis factor inhibitors/ustekinumab resistant disease. However, it is clear that the IL-17 antagonists have changed the benchmark for clinical efficacy, and it is likely that ixekizumab along with the other IL-17 antagonists are set to achieve a new standard of care in the treatment of moderate to severe plaque psoriasis. Keywords: interleukin-17, psoriasis, IL-17, ixekizumab